The reinforcement and toughening of jute/PLA (lactic acid) composite material with modified-rubber/SiO2 core-shell particles. (November 2022) - Song, X.; Zhang, Y.; Zou, T.; Li, Y.; Wang, P.; Hu, D.
Abstract: In this paper, the sol-gel method is used to prepare styrene butadiene rubber (SBR)/silica (SiO2 ) core-shell particles. A polylactic acid (PLA) composite film containing modified-SBR/SiO2 (MSBR/SiO2 ) core-shell particles was then prepared by solution casting, and then jute/PLA laminated composites were prepared by hot pressing technique. The mechanical properties of hybrid jute/PLA composite materials containing different types and mass fractions were studied. The results show that the bending fracture mode of the composite materials changed from brittle fracture to ductile fracture after adding MSBR/SiO2 core-shell particles. When 4% MSBR/SiO2 core-shell particles is combined into the PLA matrix, the bending fracture strain and maximum bending strength, respectively increase by 266.7% and 82.1%, while the elongation at break and the maximum tensile breaking strength, respectively increase by 77.8% and 333.3%. The toughening mechanism is attributable to the matrix plastic deformation caused by the addition of MSBR/SiO2 core-shell particles and the matrix cavitation caused by MSBR/SiO2 core-shell particles.